2010
DOI: 10.1002/jmv.21887
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of human papilloma virus (HPV) infection in Italian women

Abstract: HPV infection is a "necessary cause" of cervical cancer and it is sexually transmitted. Due to upcoming mass vaccination investigation on risk factors for infection is the basis to implement prophylactic strategy even in older women. The aim of the study was to evaluate predictors of high-risk (HR) HPV infection in adult women. Between 2006 and 2008, 100 women aged >18 years, with no previous treatment for cervical lesions, were screened for HR HPV infection in Rome, Italy. Risk factors for HPV infection were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(47 reference statements)
2
3
1
Order By: Relevance
“…This confirms our study (OR-5.10, p -0.042), and many other published works on this subject [13,16,17,[36][37][38]. Moscicki says that a large number of sexual partners is an independent risk factor for HPV infection and cervical cancer.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This confirms our study (OR-5.10, p -0.042), and many other published works on this subject [13,16,17,[36][37][38]. Moscicki says that a large number of sexual partners is an independent risk factor for HPV infection and cervical cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies show that the very early age of sexual initiation is not an independent risk factor for cervical cancer [14,21] or the risk is slightly elevated (on the border of statistical significance [32]). Most of the work, however, significantly stresses the influence of early initiation of sexual activity with an HPV infection [13,15,17,35]. Our study confirms the relationship between the early start of sexual activity (under 16 years of age) and HPV infection.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While several previous studies reported that smoking history is a potential predictor [ 11 14 ], others did not find any association between smoking history and HR-HPV prevalence [ 12 , 15 17 ]. As reported elsewhere [ 8 , 11 , 13 , 15 , 17 ], the OR for HR-HPV positivity was higher if subjects had more partners (either numbers in lifetime or numbers in the past 6 months). The association in our study appeared stronger (AOR for subjects with 5 or more partners, 4.72) than that in other reports (OR for a similar number of partners was in the range of 1.1–3.9).…”
Section: Discussionmentioning
confidence: 99%
“…Gita et al [12] found that the incidence of HPV infection is highest among women aged 35 to 44. Cercato et al [15] utilized questionnaires to identify the risk factors for HPV infection. Education, socioeconomic status, gynecological history, use of oral contraceptives, sexually transmitted diseases, working conditions, low body mass, low intake of vegetables, male factors, smoking, and drinking were included as items in the questionnaires.…”
Section: Agementioning
confidence: 99%